Hubungan Antara Rasa Komunitas dengan Motivasi Kerja Pengurus Subak - Prayoga, Yande; Herdiyanto, Yohanes Kartika (Jurnal Psikologi Udayana, 2014)
Subak is a traditional organization of irrigation that have been known as one of the world heritages. However, it recognition should be done with the way to accomplish real problems that happened in itself, which supposed to have particular concerns. One thing that could be done is increasing the sense of community among subak's committee so that they will have job motivation to run subak. Based on that fact, the aim of this study is to know the relationship between sense of community with job motivation among subak's committee.   Methods used in this study was quantitative research methods with product-moment correlation to do data analysis. The subjects were choosen with cluster sampling technique for the total number of 58 subjects. The measurements used were sense of community modified scales from McMillan and Chavis (1986) with 34 items (cronbach's alpha is 0,898 and validity coefficient ranged from 0,314-0,637) and job motivation modified scales from Dewi (2008) with 27 items (cronbach's alpha is 0,885 and validity coefficient ranged from 0,308-0,617).   The result of this study indicates that the correlation values of sense of community and job motivation is 0,696 with 0,00 probability (p<0,05). It explained that Ho rejected and Ha accepted. Those values indicates that there are positive and significant relationship between sense of community and job motivation of subak's comittee. In addition, determinant coefficient result is 0,484 that pointed the relative contribution among sense of community with job motivation is 48,4%. This result is similiar with the theory from Hughey, et.al. (1999) which reveals that sense of community will encouraged maningful results for organization.   Keywords: sense of community, job motivation, work motivation and subak’s committee